ANALISIS BREAK EVEN POINT SEBAGAI ALAT PERENCANAAN LABA PADA UD BUMI TANI KABUPATEN LUWU UTARA - Astriani, Wilda; s, Masnawaty; Azis, Fajriani (Jurnal Sains Riset, 2024)
This research aims to analyze the break-even point as a profit planning tool for UD. Bumi Tani in North Luwu Regency. The research variable is profit planning, measured through break-even point analysis. The study population consists of data related to break-even point analysis, including costs, sales, gross profit, and net profit for UD. Bumi Tani in North Luwu Regency during the period 2020-2022. The sample used encompasses the entire population under study, including data on costs, sales, gross profit, and net profit for UD. Bumi Tani in North Luwu Regency during the period 2020-2022. Data collection was conducted using documentation techniques and interviews. Data analysis employed the break-even point formula, margin of safety, and profit planning calculations. The research findings reveal the break-even point in 2020 amounted to Rp19,422,070,314, increasing by 34.7% to Rp26,160,792,733 in 2021, and further rising by 17.5% to Rp30,751,220,045 in 2022. The margin of safety in 2020 was 40.5%, increasing to 42% in 2021, and further rising to 45.1% in 2022. The profit planning results indicate a projected sales figure of Rp62,279,891,076 for the year 2023.